Measuring technique implementation and first recording of greenhouse gases (CO2, CH4 and N2O) at the sediment-water interface in the Rincón del Bonete reservoir, Uruguay (INNOTEC, 2022)
This work represents the first report carried out in Uruguay on the implementation of the technique to quantify greenhouse gases (GHG) and their diffusive fluxes through the sediment-water interface. The study was carry out in the Rincón del Bonete reservoir, located on the Río Negro. The applied technique made it possible to determine the GHG (CH4, CO2 and N2O) concentrations in the sediments. The CO2 and CH4 were the gases with the highest concentration per m2 of sediment. Regarding its diffusive fluxes, CO2 (max. = 1.198 mg/m2/d) was higher than CH4 (max. = 0.194 mg/m2/d) and N2O (max. = 0.02 mg/m2/ d). Although the values ​​determined are low if compared to other systems, it would be necessary to deepen the temporal and spatial studies to better assess the magnitude of the GHG flows. Due to the increase in the intensity of human activities and the effects of climate change that would promote the increase and intensity of algal blooms, it expected that, after their decomposition, the release of GHG in the reservoir would increase in the future.
Keywords: Greenhouse effect; reservoir; methanogenesis; denitrification; organic matter